Late Cretaceous infant intra-oceanic arc volcanism, the Central Pontides, Turkey: Petrogenetic and tectonic implications. (1st November 2015) - Aygül, Mesut; Okay, Aral I.; Oberhänsli, Roland; Schmidt, Alexander; Sudo, Masafumi
Graphical abstract: Highlights: An accreted infant intra-oceanic arc sequence is described. It is composed mainly of low-grade basaltic andesites and rhyolites. Metarhyolites give 94 ± 2 Ma zircon U/Pb crystallization age. The nascent arc is possibly associated with the regional SSZ ophiolites. Accretion of the arc is constrained to 69.9 ± 0.4 Ma by 40 Ar/ 39 Ar muscovite dating. Abstract: A tectonic slice of an arc sequence consisting of low-grade metavolcanic rocks and overlying metasedimentary succession is exposed in the Central Pontides north of the İzmir-Ankara-Erzincan suture separating Laurasia from Gondwana-derived terranes. The metavolcanic rocks mainly consist of basaltic andesite/andesite and mafic cognate xenolith-bearing rhyolite with their pyroclastic equivalents, which are interbedded with recrystallized pelagic limestone and chert. The metasedimentary succession comprises recrystallized micritic limestone with rare volcanogenic metaclastic rocks and stratigraphically overlies the metavolcanic rocks. The geochemistry of the metavolcanic rocks indicates an arc setting evidenced by depletion of HFSE (Ti, P and Nb) and enrichment of fluid mobile LILE. Identical trace and rare earth elements compositions of basaltic andesites/andesites and rhyolites suggest that they are cogenetic and derived from a common parental magma. The arc sequence crops out between an Albian–Turonian subduction–accretionary complex representing the Laurasian active margin and an ophiolitic mélange. Absence of continent derived detritus in the arc sequence and its tectonic setting in a wide Cretaceous accretionary complex suggest that the Kösdağ Arc was intra-oceanic. Zircons from two metarhyolite samples give Late Cretaceous (93.8 ± 1.9 and 94.4 ± 1.9 Ma) U/Pb ages. These ages are the same as the age of the supra-subduction ophiolites in western Turkey, which implies that that the Kösdağ Arc may represent part of the incipient arc formed during the generation of the supra-subduction ophiolites. The low-grade regional metamorphism in the Kösdağ Arc is constrained to 69.9 ± 0.4 Ma by 40 Ar/ 39 Ar muscovite dating indicating that the arc sequence became part of a wide Tethyan Cretaceous accretionary complex by the latest Cretaceous. Non-collisional cessation of the arc volcanism is possibly associated with southward migration of the magmatism as in the Izu-Bonin-Mariana arc system.